MONITORING OF INDUSTRIAL PROCESS USING INTELLIGENT TOMOGRAPHY SYSTEM - KIONG, CHAI YU (Universiti Teknologi Petronas, 2006)
In any process industries, direct analysis of processes is very important for process control system implementation and improvement. To direct analysison the processes, a real time process monitoring is required. Conventional methods of process monitoring system works by attached sensors inside the pipeline or vessel. Flow influence problem occurs when exist of sensor inside the pipeline. Solution for flow influence problem can be solved by using Electrical Process Tomography system. Electrical Process Tomography system using numbers of thin electrode plate as a sensor, and it is attached inner or outer surface of the pipeline (depend to the type of Tomography technique) to minimize the influence to the flow. This project with title "Monitoring of Industrial Process Using Intelligent Tomography System" will have objectives to study of Electrical Resistance Tomography (ERT) and develop a simple data acquisition system for ERT system. The outcomes of this project will be series of experiment results on practical of ERT technique and a working data acquisition system that able to records acquired data in a PC.